Valproic Acid Stimulates Hippocampal Neurogenesis via Activating the Wnt/β-Catenin Signaling Pathway in the APP/PS1/Nestin-GFP Triple Transgenic Mouse Model of Alzheimer’s Disease - Zeng, Qinghua; Long, Zhimin; Feng, Min; Zhao, Yueyang; Luo, Shifang; Wang, Kejian; Wang, Yingxiong; Yang, Guang; He, Guiqiong (Frontiers in Aging Neuroscience, 2019)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by the deposition of amyloid-β (Aβ) peptides and neurofibrillary tangles (NFTs) and massive loss of neuronal cells in the brain. Adult hippocampus continuously generates new neurons throughout life to shape brain function and impaired neurogenesis may contribute to a series of cognitive deterioration associated with AD. Enhancing endogenous neurogenesis represents a promising strategy that may ameliorate AD-associated cognitive defects. However, neurogenesis-enhancing approaches and underlying mechanisms are still not well studied. Here, using a mouse model of AD (APP/PS1/Nestin-GFP triple transgenic mice, 3×TgAD), we examined the effects of 4 weeks of valproic acid (VPA) treatment on hippocampal neurogenesis in 2- and 6-month-old mice. VPA treatment increased cell proliferation and the density of immature neurons in the dentate gyrus of the hippocampus of 3×TgAD mice. Consistent with enhanced neurogenesis, behavioral and morphological analysis showed that VPA treatment improved the learning and memory ability of 3×TgAD mice. Mechanistically, VPA treatment increased β-catenin levels, accumulated the inactive form of GSK-3β, and induced the expression of NeuroD1, a Wnt target gene involved in neurogenesis, suggesting the activation of the Wnt signaling pathway in the hippocampus of 3×TgAD mice. Our findings indicate that VPA stimulates neurogenesis in the adult hippocampus though the Wnt pathway, highlighting VPA as a potential therapeutic for treating AD and related diseases.